The effect of sucrose concentrations and different types of tube cap on in vitro growth of Dahlia (Dahlia sp.) using vermiculite as substrate - Rudiyanto Rudiyanto; Betalini Widhi Hapsari; Deritha Ellfy Rantau; Tri Muji Ermayanti (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.